The Effect of Skin Contact on Maternal-infant Attachment Behaviors in Emotional, Proximity-seeking, and Caretaking Dimensions in Planned and Unplanned Pregnancies in 2017, Iran: A Research - Eslaminia, Tahere; Kaviani, Maasumeh; Akbarzadeh, Marzieh (Current Women's Health Reviews, 2020)
Background: Unplanned pregnancy is a potential danger for women’s lives in the reproduction ages. Objective: The present study aimed to compare planned and unplanned pregnancies regarding the maternal-infant attachment behaviors in emotional, proximity-seeking, and caretaking dimensions. Methods: The present analytical case-control study was conducted on 140 women who had given birth to their children in the hospitals affiliated to Shiraz University of Medical Sciences in 2017. The participants were divided into planned and unplanned pregnancy groups. Within the first hour and 24 hours after birth, the babies were put naked in skin-to-skin contact with their mothers for 15 minutes and the study questionnaire was completed. The data were collected using the Avant checklist. P<0.05 was considered to be statistically significant. Results: The mean score of attachment in the early hours was 84.22±12.59 in the planned pregnancy group and 74.28±15.81 in the unplanned pregnancy group, and the difference was statistically significant (p<0.001). However, no significant difference was observed between the two groups in this regard after 24 hours (p=0.122). Additionally, the results revealed a significant difference between the two groups concerning emotional (p<0.001) and caretaking (p=0.007) behaviors. However, no significant difference was found between the two groups regarding the three behaviors after 24 hours. Emotional (talking and smiling, p=0.001), proximity-seeking (circling one’s arms around the baby, p=0.001), and caretaking (paying attention to the baby, p=0.001) behaviors were significantly more observed in the two groups in the early hours and the first 24 hours. Conclusions: Mother’s skin-to-skin contact with her baby during lactation increased attachment in unplanned pregnancies after 24 hours.
Keywords: behavior